2012
DOI: 10.1002/jctb.2728
|View full text |Cite
|
Sign up to set email alerts
|

The addition of ethanol as defoamer in fermentation of rhamnolipids

Abstract: BACKGROUND: Rhamnolipids biosurfactants mainly produced by Pseudomonas aeruginosa have a wide range of potential applications. However, production of rhamnolipids on a large scale is constrained by severe foaming in fermentation. This study addressed the applicability of organic solvents as both defoamer and carbon substrate in rhamnolipids fermentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…The superior demulsification ability of rhamnolipids to that of chemical surfactants like sodium dodecyl sulfate, etc. might be due to their much higher surface activity (Sha et al, 2012b), which have been suggested to benefit the breakup of the interfacial film as well as the coalescence of droplets (Kim and Wasan, 1996). In view of costefficiency, rhamnolipid at 1000 mg/L was selected for subsequent researches in demulsifying waste crude oil.…”
Section: Demulsification Of Waste Crude Oil By Rhamnolipidsmentioning
confidence: 99%
“…The superior demulsification ability of rhamnolipids to that of chemical surfactants like sodium dodecyl sulfate, etc. might be due to their much higher surface activity (Sha et al, 2012b), which have been suggested to benefit the breakup of the interfacial film as well as the coalescence of droplets (Kim and Wasan, 1996). In view of costefficiency, rhamnolipid at 1000 mg/L was selected for subsequent researches in demulsifying waste crude oil.…”
Section: Demulsification Of Waste Crude Oil By Rhamnolipidsmentioning
confidence: 99%
“…Rhamnolipids have typically been produced by aerobic fermentation systems with high agitation and submerged sparging of fine oxygen or air bubbles [15][16][17][18]. Extensive and stable foaming occurs in such systems and causes serious operational problems such as wall growth of cells, overflow of foams, clogging of gas outlet filters, and higher chance of contamination [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant was taken for measuring rhamnolipid content using the anthrone-sulfuric assay [26] while the sediment was suspended in deionized water for detecting the cell content. The absorbance was then measured at 650 nm using water as a blank [27]. Optical density (OD 650 ) was converted to the cell concentration by a standard curve.…”
Section: Rhamnolipid Fermentationmentioning
confidence: 99%